IMPLEMENTING WORD WALL STRATEGY IN TEACHING WRITING DESCRIPTIVE TEXT FOR JUNIOR HIGH SCHOOL STUDENTS - Ratu Sartika (Journal of English and Education, 2017)
The research was aimed at investigating the use of Word Wall Strategy in helping junior high school students learn writing descriptive texts and students’ opinions toward the implementation of Word Wall Strategy in teaching writing descriptive text. The descriptive qualitative method was employed in this study. The data were obtained through observation, questionnaire, and document as the instruments of the research. The use of Word Wall as the strategy in teaching writing a descriptive text was helpful for junior high school students by facilitating teacher and students to carry out all of the steps in implementing Word Wall Strategy proposed by expert. The result also displayed that Word Wall Strategy have important roles in helping students learn to write a descriptive text with more than 50% responses were positive regarding the students’ responses to the use of Word Wall. In the end, based on the result of the study, delivering Word Wall strategy is recommended to be implemented in junior high school’s classroom.